DESIGNING BEACHSIDE RESORT AT PANTAI INDAH KALANGAN, CENTRAL TAPANULI WITH VERNACULAR ARCHITECTURE APPROACHMENT - Imam Faisal Pane; Maria Isabella Zebua (Jurnal Koridor, 2019)
Central Tapanuli is known for many stunning tourist locations, mainly its stretch of beach so that it becomes a great potential as an area of tourism with adequate accommodation as well as resorts. Some problems in the design resort that attract the attention and interest of tourist to come, how to design space programs according to human needs in it, and how to design buildings that are responsive to local climate, cultural and social conditions. From these problems, it is intended to create resorts with a variety of recreational facilities, design inner spaces and outdoor spaces according to resorts needs and local wisdom, and can introduce local culture to foreign tourists through resort design. Therefore, the research conducted by collecting existing location information, literature studies, comparative studies, and field surveys. After doing each step above, the result obtained, namely the design of the Beachside Resort using vernacular architecture, which is applied to each form of resort building, ranging from hotel, restaurant, cottages, spa and sauna, and other supporting facilities, using the types of the Central Tapanuli household, combined with the application of â€œDalihan Natoluâ€. By obtaining these result, it is expected to become tourism locations and become a positive response in bringing back the traditional architecture of Central Tapanuli.